ESTUDO DAS ANGULAÇÕES E INCLINAÇÕES DENTÁRIAS OBTIDAS NO TRATAMENTO ORTODÔNTICO COM A UTILIZAÇÃO DA PRESCRIÇÃO MB - Bastia, Fernanda Marcondes Machado (2005)
This current study aims at verifying the dental angulation and the tipping at the end of an orthodontic treatment in cases treated with fixed appliance and the MBT prescription, and comparing them to the values found by Andrews for a natural normal occlusion. Thirty pairs of final cast models of thirty patients with average age between 13 and 23 years of age were used. As a requirement, these patients should not have undergone any kind of orthopedic intervention, they should not have used intermaxillary elastics, presented dento-alveolar compensation or being treated with extraction. In order to measure the mesiodistal angulation and the buccolingual tipping, a device manufactured in a previous research study aiming at taken these measurements was used. According to the methodology applied and to the results achieved, it can be concluded that the angulation of the dental crowns, for both upper and lower arches, presented positive values. As for the inclination of the dental crowns, in both dental arches, positive values were found for the central and the lateral teeth, whereas, canines, premolars, incisors, and first molars presented negative values. Individual variations were found in both measurements. Comparing the results achieved in this research study to the ones found by Andrews, statistical differences were verified for the majority of teeth, in both measurements taken in the study.